ANALISIS MOTIVASI BELAJAR IPA PADA PEMBELAJARAN E-LEARNING SISWA KELAS VII SMP MUHAMMADIYAH 1 PONTIANAK - Safitri Anggraeni; Hanum Mukti Rahayu; Anandita Eka Setiadi (FKIP UM Pontianak, 2022)
The government's policy to eliminate face-to-face learning requires that learning be done online or e-learning. This study aims to analyze the motivation to learn science in e-learning class VII SMP Muhammadiyah 1 Pontianak. This research is descriptive qualitative, the primary data source in this study is the result of a questionnaire on learning motivation by e-learning, the secondary data source is the result of interviews with science teachers. Based on the results of questionnaires and interviews of students' learning motivation in e-learning learning shows the percentage of student motivation per category, namely the strong ability of 71.83%, moderate ability of 25.35% and very strong ability of 2.82%. The indicators that have the highest percentage value are the first activities that are interesting in learning, namely 66.44%, the second hopes and aspirations for the future are 66.42%, the third desire and desire to succeed are 64.37%, the four encouragements and needs in learning is 64.22%, and the five conducive environment is 63.7%. From the results of the study, it can be concluded that the motivation to learn science in e-learning learning for class VII students of SMP Muhammadiyah 1 Pontianak has a strong motivation category.